Notas sobre algunas inscripciones paleohispánicas (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
New readings and interpretations of some words occurring on various Celtiberian and Iberian inscriptions.
Keywords: Epigrafía romana; Toponimia; Epigrafía paleohispánica; Hispania; Celtíberos; Microtoponimia